Nordic Preschool Teachers’ Views of the Physical and Psychological Literacy Environments Regarding Read-Alouds - Tarja Alatalo; Maria Magnusson; Martina Norling (Nordisk Barnehageforskning)
This research aims to increase knowledge about how preschool teachers in three Nordic countries view their preschool’s physical and psychological literacy environment regarding read-alouds. A total of 222 Nordic preschool teachers (52 Finnish, 91 Norwegian, and 79 Swedish) responded to a survey about early literacy practices. Likert-scale questions that contained statements about teachers’ views of the physical literacy environment and methods of reading aloud were used. Scales indicating a physical and psychological literacy environment were created based on statements that reflected the respective literacy environment. The results revealed that the teachers, on average, rated their preschool’s physical literacy environment positively. Their attitudes towards the psychological literacy environment were, on average, high regarding reading aloud as an opportunity for meaning-making and even higher for language-stimulating interaction. The attitudes towards reading aloud to organise everyday activities scored very low on average, which was a somewhat unexpected finding. There were some statistically significant differences in the measures between countries and groups, such as educational level. Emphasising high-quality literacy environments as early as for one- to three-year-old children is discussed as being essential in preschool teacher training and in-service training.